2019
DOI: 10.1016/j.jval.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Dependency: A Challenge for Health and Social Care Planning—Observational Stroke Cohort

Abstract: Background: After a stroke, families require the coordinated assistance of health and social care. Currently there is a lack of comprehensive evaluation and assessment tools to identify discharge needs, and there is separate management of health and social resources, and access to these services is variable between regions. Objective:The main objective of this study was to assess the factors associated with risk of dependency after stroke and propose a suitable instrument for identifying patients at higher ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
6
0
3
Order By: Relevance
“…UU.) Van Meijeren-Pont et al, 2021 (Netherlands) 42 Estudio prospectivo de cohortes B 313 pacientes Costes RHB hospitalaria vs. domiciliaria ( SCORE Study ) un año postictus Hospitalaria: 68.545,88 €/paciente/año Domiciliaria 26.673,29 €/paciente/año Queralt Tomas et al, 2019 (España) 44 Longitudinal prospectivo de cohorte comunitaria C 233 pacientes Indicadores pronóstico de discapacidad sociosanitaria 2 años postictus. Dependencia residual 50,6% casos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…UU.) Van Meijeren-Pont et al, 2021 (Netherlands) 42 Estudio prospectivo de cohortes B 313 pacientes Costes RHB hospitalaria vs. domiciliaria ( SCORE Study ) un año postictus Hospitalaria: 68.545,88 €/paciente/año Domiciliaria 26.673,29 €/paciente/año Queralt Tomas et al, 2019 (España) 44 Longitudinal prospectivo de cohorte comunitaria C 233 pacientes Indicadores pronóstico de discapacidad sociosanitaria 2 años postictus. Dependencia residual 50,6% casos.…”
Section: Resultsunclassified
“…Los principales determinantes 36 , 37 , 38 , 39 de los costes del primer año son la hospitalización (48,5%) por reingresos adicionales y el tratamiento farmacológico 40 , 41 , y la rehabilitación (33%) 18 , 42 , 43 . El coste anual medio del primer año es de 29.484 €, de los que 74% se concentra en los primeros seis meses y en el caso de la rehabilitación domiciliaria el servicio se encarece 2,5 veces 44 . Los pacientes con mayor discapacidad (≥ 3 Rankin) tienen un coste más elevado (8.500 €) que los pacientes sin discapacidad (6.000 €).…”
Section: Resultsunclassified
“…Few of which qualify to be reported here in order to establish hard ground of the study in hand e.g. studies like: safety and risk management including: pharmacy role in health system of Colombia (Amariles et al, 2020), Mount Sinai health system in US (Buckley et al, 2020), health services system of Hubei, China (Chen et al, 2020), examine psychosocial risk factors in public workplace in Denmark (Dahler-Larsen et al, 2020), vexed Greek health care system (Kapetanakis et al, 2020), resilience of Spanish health system (Legido-Quigley et al, 2020), strained Latin American health care system (Navarro et al, 2020), challenges facing in health and social care planning in Spain (Queralt-Tomas et al, 2019) and safety risk management and occupational health of waste management firms in Portugal (Ramos et al, 2020). Aghdam et al (2020) carried a detailed study on effective usage of Internet of Things (IoT) to facilitate the paramedical staff and health workers and also to identify the major trends and challenges facing the healthcare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study demonstrated a rate of transition to dependency in a high proportion of patients beyond the rehabilitation of 11 provided. All patients have a greater need for health surveillance and community support after hospital discharge [11].…”
Section: Introductionmentioning
confidence: 99%